Respuesta :

Answer:

y = (x +2)(x -1)(x -3) . . . . or . . . . y = x³ -2x² -5x +6

Step-by-step explanation:

The graph shows y=0 at x=-2, x=1, and x=3. These are called the "zeros" or "roots" of the function, because the value of the function is zero there.

When "a" is a zero of a polynomial function, (x -a) is a factor. This means the factors of the graphed function are (x -(-2)), (x -1) and (x -3). The function can be written as the product of these factors:

... y = (x +2)(x -1)(x -3) . . . . . the equation represented by the graph

Or, the product can be multiplied out

... y = (x +2)(x² -4x +3)

... y = x³ -2x² -5x +6 . . . . . the equation represented by the graph